Colonial people - Howarth, Sarah; McNeill, Philip (Brookfield, Conn. : Millbrook Press, 1994)
A description of the everyday lives of thirteen colonial people through the use of quotations and illustrations of the time.
Includes bibliographical references and index.
9 - 12 years
Keywords: United States -- Social life and customs -- To 1775